Advertisements in Various Television Channels on Food items & Understandability of Telecasted Programs Influencing Nutritional Status of Urban Graduate Mothers - Begum, Ayesha; Zebsyn, Sonia; Bhuyan, Md Aminul Haque (Bangladesh Journal of Nutrition, 2013)
A descriptive cross sectional study was carried out amongst eighty graduate mothers having U-5 years children from different socio-economic groups of Mohammadpur area in Dhaka city. They were interviewed on nutrition related programs thorough television. The purpose of the study was to determine the impact of advertisements and understandability of nutrition education programs through different TV channels among the respondents and also the impact of these programs on maternal and child nutrition (MCN). Results of the study showed that the programs of mass media like TV on nutritional aspects influence the nutritional awareness of the respondents. Most of the graduate mothers practiced extra diet as special food taken during pregnancy and lactation period of which television was the major source of knowledge compared to radio, newspaper, doctor and family members. Again 52.5% respondents were normal along with 33.8% respondents were overweight and rests of 13.7% mothers were obese. Furthermore, 82% U5Cs nutritional status were normal whereas only 3% were found in border line according to MUAC. Few U-5 children were found overweight by WAZ. So adult and child overweight are increasing day by day in urban areas which need great attention to prevent chronic diseases. From this study, it was revealed that no relationship exist between family income and nutritional status of the respondents and also between the educational level and nutritional status of them (P value > 0.05). It may be concluded from the study that the exposure to nutrition related programs through different television channels had a role to improve the nutritional status. DOI: http://dx.doi.org/10.3329/bjnut.v24i0.14037 Bangladesh J. Nutr. Vol. 24-25 Dec 2011-2012 pp.65-76